Guidelines for Academic Information System Management in Educational Institutions under the Office of Khon Kaen Primary Educational Service Area 2 - Jinalak, Sunattha; Piampuechana, Niyada (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The purposes of this research were to study the current situation, the desirable condition and guidelines for academic information system management in educational institutions under KhonKaen Primary Educational Service Area Office 2.The sample group used in this research consisted of school administrators, teachers who are responsible for academic information system management in educational institutions and academic teachers under KhonKaen Primary Educational Service Area Office 2 with the total number of 141 people. The tool used for data collection was a 5-level.The statistics used for data analysis comprised percentage, frequency, mean and PNI modified index. The research results were found that: 1. The current situation of academic information system management in educational institutions under KhonKaen Primary Educational Service Area Office 2, in overall, was rated at a moderate level, and the desirable condition of academic information system management in educational institutions under KhonKaen Primary Educational Service Area Office 2, in overall, was found at the highest level and PNI modified index of academic information system management in educational institutions under KhonKaen Primary Educational Service Area Office 2 was found that the aspect with the highest need was the development of learning process, followed by evaluation and credit transfer, while the least important aspect was educational supervision. 2. Guidelines for academic information system management in educational institutions under the Office of KhonKaen Primary Educational Service Area 2 were found as follows: 1)The administrators should examine information about learning design process consistent with the potential and context of the learners. 2) The administrators should collect information, evidence, academic documents showing development and students' grades. 3)The administrators should apply information to measure and evaluate to prepare documents for document 1-7 4) The administrators should improve curriculum of educational institutions to be suitable with information technology storage for curriculum development clearly, definitely and easily for searching. 5)The administrators should present information of information technology in form of documents, journals, brochures, information signs, analyze data from monitoring, supervision results.